Functional encapsulation of laser melted Inconel 718 by Arc-PVD and HVOF for post compacting by hot isostatic pressing. (31st October 2015) - Tillmann, W.; Schaak, C.; Nellesen, J.; Schaper, M.; Aydinöz, M. E.; Niendorf, T.
Abstract : In this study, the Selective Laser Melting (SLM) technology was used to manufacture flat specimens from Inconel 718 powder. The SLM process parameters have a major impact on the microstructure as well as on the mechanical properties of the fabricated specimens. Despite using optimized processing parameters, defects like pores cannot be completely avoided. These pores act as stress raisers and lead to premature crack initiation under cyclic loading, eventually reducing the fatigue strength of the material. Hot Isostatic Pressing (HIP) offers the possibility to eliminate the porosity and thus to increase the fatigue performance of the material. HIP combines high pressure and high temperature to produce materials with superior properties. Unfortunately, open porosity, i.e. open pores on the surface, can prevent full densification. In the present work, SLM flat specimens were encapsulated by means of Cathodic Arc Deposition (Arc-PVD) and High Velocity Oxygen Fuel Spraying (HVOF) to seal open pores. For this purpose, different encapsulation materials were investigated with a focus on materials offering additional functions such as an improved high temperature corrosion resistance or applicability as a bond coat for thermal barrier coatings.